Different Route of Deliveries Vitamin C: Current Update on Knowledge and Perception among the Community in Malaysia - Nurhani Syazni Yusoff; Syarifah Syamimi Putri Adiba Syed Putera; Ahmad Yasser Hamdi Nor Azlan (Asian Journal of Medicine & Health Sciences, 2022)
Background: Products containing vitamin C have been widely used in aesthetics, but limited research has been conducted to assess the knowledge and perception of the community in Malaysia regarding vitamin C and its delivery routes in aesthetics. Vitamin C can be delivered to the human skin in various forms that appear to be popular among the community for their beauty benefits. Previous studies have found a beneficial effect in ultraviolet (UV) irradiation protection in formulations containing vitamin C and vitamin E. This study aimed to identify the current update on the usage pattern of vitamin C, the community’s knowledge of vitamin C, and the community’s perception regarding different routes of vitamin C delivery in aesthetics. Methods: A cross-sectional study design was used using a self-administered online questionnaire. The number of participants included in the study were 385 participants. The data was collected and analysed using SPSS version 21 and presented as frequency and percentage. Results: The findings revealed that 98.7% of respondents understand what vitamin C is including its functions, recommended intake, vitamin C sources etc and 82.3% have used vitamin C products. This study also highlighted moderate knowledge of vitamin C among respondents (49.1%) and moderate perception of different routes of vitamin C delivery in aesthetics (54%). Conclusion: The Malaysian community has a favourable opinion of vitamin C products which provide various skin benefits. It is recommended that future studies target a larger population and more diverse socio-demographic characteristics to evaluate knowledge and perception of vitamin C use and its routes of delivery.